FTIR, 1H, and 13C NMR Characterization and Antibacterial Activity of the Combination of Euphorbia Honey and Potato Starch - Ahmed, Moussa; Amirat, Mokhtar (Combinatorial Chemistry & High Throughput Screening, 2024)
Aim and Objective: In recent years, natural biopolymer (potato starch) hydrogels have been widely used in the field of wound dressing material. This study aimed to develop and characterize a novel antibacterial hydrogel made from potato starch and natural honey. Methods: The structure of the composite films was evaluated by Fourier transform infrared (FTIR) and 1H,13C nuclear magnetic resonance (NMR) spectroscopy, and the antibacterial activities were tested by agar diffusion method. FTIR analysis showed chemical interaction between the components of Euphorbia honey (EH) and potato starch hydrogel (PSH). Results: The 1H-13C NMR and FTIR analyses of EH/PSH confirmed their structure and showed the presence of glucose and hydrocarbon derivatives. After 24 h of incubation, the EH/PSH hydrogel showed good antibacterial activity against three bacterial strains (K.pneumonia, P.mirabilis, and P. aeruginosa) by producing clear inhibition zones of 12.33 ± 1.88 mm, 15.33 ± 0.94, and 10 ± 0 mm, respectively. In addition, K. pneumonia, P. mirabilis, and P. aeruginosa were sensitive to the EH/SPH with a minimum inhibitory concentration (MIC) of 1 %. Conclusion: These results suggest that EH–PS has potential as an alternative candidate to conventional antibiotics.
Keywords: NMR